Research progress on molecular mechanisms of phosphate starvation response in plants - LIU Rong; LI Bingjie; WANG Zhiye (浙江大学学报. 农业与生命科学版)
Phosphorus (P) is one of the essential macronutrients for plant growth and development. Plants absorb phosphorus from the soil mainly in the form of inorganic phosphate (Pi). However, Pi in the soil is easily fixed, and its availability is low. Therefore, it is of great significance to study the molecular mechanisms of Pi starvation response (PSR) for improving the effective utilization of P in crops. In the past 20 years, great progress has been made in the study of the regulatory mechanisms of plant responses to Pi deficiency. Here, we systematically reviewed the research progress achieved in recent years both domestically and internationally, including local PSR signaling-mediated alteration of root morphogenesis, the PHR (PHOSPHATE STARVATION RESPONSE)-SPX (SYG1/Pho81/XPR1)-centered systemic PSR signaling network, the molecular mechanism of the symbiosis of rice arbuscular mycorrhizal fungi under Pi stress conditions, the transportation and allocation of Pi from rhizospheres to shoots, and the relocation and reuse of Pi from leaves to seeds. Finally, we discussed the future research priorities on the molecular mechanisms of PSR. This review summarizes current results and looks forward to future research directions to facilitate the study of PSR in plants and the improvements of Pi utilization efficiency in crops.